Programação fetal: impactos da variação de peso da vaca gestante sobre sua progênie - Rodrigues, Leonel da Silva (2019)
The objective of the present study was to evaluate the effects of cow weight changes during development gestation, carcass and meat characteristics, empty body components and progeny reproductive performance. Data collected from beef cows and their offspring, born between 2002 and 2013, were used for confinement at 24 months of age in males and mated at 24 months of age in females. The treatments studied were: Weight gain (GA): pregnant cows that gained from 0.0 to 15.0% of body weight during pregnancy; Moderate weight loss (PM): pregnant cows that lost 0.1 to 15.0% of body weight during pregnancy; Severe weight loss (PS): pregnant cows that lost 15.1 to 30.0% of body weight during pregnancy. The highest slaughter weights were obtained in treatments GA and PM, 428 and 424 kg, respectively. The lowest weight was registered in the PS treatment, 406 kg. Moderate and severe weight loss during pregnancy increases the relative spleen weight of male offspring, with relative weights of 0.36 and 0.34 kg/100 kg of PCVZ for PM and PS, in that order and 0.29 kg/ 100 kg PCVZ for the GA. Kidney and intestine participation in empty body weight is higher in male offspring of pregnant cows who have severely lost weight. The relative weight of kidneys was higher in PS (0.23 kg/100 kg PCVZ) than in GA (0.20 kg/100 kg PCVZ) and PM (0.21 kg/100 kg PCVZ). Cow weight variation during pregnancy does not influence the internal fat participation in male offspring. At 210 and 365 days of age, the animals from treatment GA (135.26 and 211.67 kg) and PM (128.89 and 210.98 kg) presented higher weight than animals from PS (119.25 and 197.27 kg). Slaughter and hot carcass weights were higher in GA (434 and 240 kg) and PM (433 and 238 kg) animals than in PS (407 and 223 kg) animals. The GA and PM presented carcasses with higher compactness (1.90 kg cm-1) than the PS treatment (1.80 kg cm-1). Cow weight gain during pregnancy increases the degree of marbling in the meat and the area of Longissimus dorsi of male offspring. The female offspring of cows that gain weight during pregnancy have higher weight and percentage of adult weight at 7 and 18 months of age. In the first reproductive season, PS showed a tendency of higher pregnancy rate (69.8%). GA and PM showed a lower pregnancy rate (50.0 and 59.9%). In the second reproductive season, the offspring of cows that lost more weight show higher birth weight of calves. In the third breeding season, GA showed a higher pregnancy rate (64.3%), lower productive efficiency (13.5 kg calves/kg cow) and higher calf production index (57.7 kg calf/cow).